The use of technical vision in flexible production systems to determine coordinates of randomly located objects - K. V. Averkov; D. S. Makashin (Омский научный вестник)
The article is devoted to the development of an object recognition algorithm using technical vision using Python and the OpenCV computer vision library. The article presents a program that allows you to set the coordinates of an object arbitrarily located in the field of view of the camera, as well as determine its orientation. This data will allow you to perform an effective capture of the object by the grip of the manipulator. In modern mechanical engineering, tasks of this kind are quite relevant, they make it possible to increase the autonomy of flexible production systems and make production safer.